2011
DOI: 10.1111/j.1365-2621.2011.02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of aroma compounds from Zhenjiang aromatic vinegar by supercritical fluid extraction

Abstract: Zhenjiang aromatic vinegar, which is produced from sticky rice through solid-state fermentation, is highly prized as one of the four famous China-style vinegars, owing to its unique flavour. In this study, a method of supercritical fluid extraction (SFE) was used for the first time to recover aroma compounds from Zhenjiang aromatic vinegar. For this purpose, the optimal conditions for the extraction of aroma compounds by SFE were determined as follows: CO 2 flow rate, 25 L h )1 ; extraction time, 2 h; extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…H e t e r o c y c l i c c o m p o u n d s , s u c h a s f u r f u r a l , tetramethylpyrazine, trimethylpyrazine and furfural alcohol, and phenols were first quantified in SAV in our studies, which were only identified and semi-quantified in the literature (Lu et al 2011;Xiao et al 2011). Among heterocyclic compounds, the concentration of tetramethylpyrazine was the highest, which was 127.13 mgL −1 .…”
Section: Volatile Profile Of Vinegar Samplesmentioning
confidence: 66%
See 1 more Smart Citation
“…H e t e r o c y c l i c c o m p o u n d s , s u c h a s f u r f u r a l , tetramethylpyrazine, trimethylpyrazine and furfural alcohol, and phenols were first quantified in SAV in our studies, which were only identified and semi-quantified in the literature (Lu et al 2011;Xiao et al 2011). Among heterocyclic compounds, the concentration of tetramethylpyrazine was the highest, which was 127.13 mgL −1 .…”
Section: Volatile Profile Of Vinegar Samplesmentioning
confidence: 66%
“…Among heterocyclic compounds, the concentration of tetramethylpyrazine was the highest, which was 127.13 mgL −1 . Tetramethylpyrazine accounted for 6.77 % of volatile compounds of Zhenjiang aromatic vinegar (Lu et al 2011). The concentration of furfural ranged from 20.14 to 88.39 mgL −1 .…”
Section: Volatile Profile Of Vinegar Samplesmentioning
confidence: 99%
“…A total of 44 aroma compounds were identified in Zhenjiang aromatic vinegar SFE extract. Acetic acid (15), ethyl acetate (16), furfural (17), phenethyl alcohol (18), tetramethylpyrazine (19), 3-hydroxy-2-butanone (20) and benzaldehyde (21) were the main aroma compounds in the vinegar SFE extract (Figure 3) [46].…”
Section: Supercritical Fluid Extraction Of Flavorsmentioning
confidence: 99%
“…Acetic acid, ethyl acetate, furfural, phenethyl alcohol, tetramethylpyrazine, 3-hydroxy-2-butanone and benzaldehyde and 44 other aroma compounds were identified in Kozu vinegar 14 . Fraglide-1 is a furanone compound which comes from sticky rice husk.…”
Section: Resultsmentioning
confidence: 99%
“…After leaching the process, a decoction process is conducted to pasteurize the vinegar before further storage. During this step, a series of reactions may occur like the Maillard reaction, decomposition, degradation and esterification 13,14,32 .…”
Section: Resultsmentioning
confidence: 99%